Performance of Cellular Bucket Brigades with Hand‐Off Times. Issue 10 (17th July 2017) - Lim, Yun Fong
Abstract : A cellular bucket brigade is a way to coordinate workers along an aisle with work content on both sides. Each worker in a cellular bucket brigade works on one side of the aisle when he proceeds in one direction, and he works on the other side when he proceeds in the reverse direction. Although the cellular bucket brigade eliminates the unproductive walk‐back, it requires more hand‐offs to assemble a product than a traditional (serial) bucket brigade. These hand‐offs may waste significant production capacity as each of them requires an exchange of work, which can be complicated and time‐consuming in practice. This motivates us to investigate the impact of hand‐off times on the cellular bucket brigade's performance. We identify sufficient conditions to ensure no workers are idle in the long run and for the system to self‐balance in a model with hand‐off times. Our results suggest that even with significant hand‐off times, the cellular bucket brigade can remain substantially (about 50%) more productive than the traditional bucket brigade especially if the team size is small and the workers' work velocities are close to their walk velocity.